EZ-Arabic : a virtual learning resource tool for Malaysian primary schools - Sahrir, Muhammad Sabri; Nasir, Mohd Shahrizal; Yahaya, Mohd Firdaus (2014)
This innovation features a virtual Arabic learning tool prototype, which is specifically designed for learners at primary schools in Malaysia. This expanded Arabic virtual learning tool prototype enables teachers and students access to additional Arabic language learning aids, and complementing traditional learning methods. The prototype provides a new learning experience for students who have been through a traditional Arabic teaching and learning methods, by immersing into the attractive, interesting and interactive virtual learning environment. It facilitates Arabic learning enhancement through a compendium and a variety of open-sources learning tools such as the followings: (a) Ebooks, (b) Educational Arabic games, (c) Audio and visual learning aids in Arabic, (d) Online dictionary and translator for Arabic, (e) Online chat-box for virtual discussion, and (f) Links of various websites in learning Arabic for children.